Il Museo di Storia Naturale dell'Università di Firenze - Le collezioni botaniche Le collezioni botaniche - Mauro Raffaelli (Cataloghi e collezioni, 2009)
The Natural History Museum of the University of Florence, founded in 1775 by Grand-Duke Pietro Leopold, is the oldest scientific museum in Europe. With this second volume on the Botanical Collection, Florence University Press continues its series dedicated to the six Sections of the Museum. The first part of the volume recounts the birth of botanical sciences in Florence and the history of the museum collections from sixteenth century to today. Then follows the second part which describes the historical and modern Herbaria, for each of which the main events that went to their formation, the importance of the plants they contain and biographical information on those who built the collections are described. The third section expounds the other collections in the Botanical Section of the Museum, among which of particular interest are the wax models of plants and fruits, manufactured by the old Grand-ducal Ceroplastics Laboratory, the wood collection, plaster of Paris mushrooms and the eighteenth century still life paintings of fruits and vegetables by Bartolomeo Bimbi. Finally, the last part illustrates the importance that herbaria play today in modern scientific research, drawing attention to the fact that they are an archive that holds taxonomical, chorological and ecological information in function of the plants they contain, as well as historical-biographical information on the scholars who, through their efforts, built up the collections.